Second order sliding power control for a variable speed-constant frequency energy conversion system - Valenciaga, Fernando (2010)
This paper presents a decoupled active and reactive power control for a variable speed-constant frequency generation system based on a brushless doubly fed reluctance machine. The control design is approached using multi-input second order sliding techniques which are specially appropriate to deal with nonlinear system models in presence of external disturbances and model inaccuracies. The controller synthesized through this theoretical framework presents very good robustness features, a finite reaching time and a chattering-free behavior. The performance of the closed loop system is assessed through representative computer simulations.